Diagnosis and Management of Hepatic Encephalopathy A Case-based Guide (Springer International Publishing, 2018)
This volume provides a comprehensive, state-of-the-art overview of hepatic encephalopathy. Through a case-based approach, the text reviews new data and studies about the role of microbiota in liver disease and hepatic encephalopathy, explores the burden of hepatic encephalopathy on readmissions, costs, and patient care, and highlights management strategies for patients in differing stages of hepatic encephalopathy. Exploratory new therapies and treatment targets are also discussed in the guide. Written by experts in the field, Diagnosis and Management of Hepatic Encephalopathy: A Case-based Guide is a valuable resource for physicians and researchers who deal with this challenging complication of cirrhosis.